Ear Asymmetry and Contextual Influences on Speech Perception in Hearing-Impaired Patients - Moulin, Annie (Frontiers in Neuroscience, 2022)
The left hemisphere preference for verbal stimuli is well known, with a right ear (RE) advantage obtained when competing verbal stimuli are presented simultaneously, at comfortable intensities, to both ears. Speech perception involves not only the processing of acoustic peripheral information, but also top down contextual influences, filling the gaps in the incoming information, that is particularly degraded in hearing-impaired individuals. The aim of this study was to analyze the potential asymmetry of those contextual influences on a simple speech perception task in hearing-impaired patients, in light of hemispheric asymmetry. Contextual influences on disyllabic word perception scores of sixty hearing-impaired patients were compared between left ear (LE) and RE, in a balanced design, involving two repetitions of the same task. Results showed a significantly greater contextual influence on the RE versus the LE, and for the second repetition versus the first one, without any interaction between the two. Furthermore, the difference in contextual influences between RE and LE increased significantly with the RE advantage measured by a dichotic listening test, in absence of any significant correlation with hearing threshold asymmetry. Lastly, the contextual influence asymmetry decreased significantly as age increased, which was mainly due to a greater increase, with age, of contextual influences on the LE versus the RE. Those results agree with the literature reporting a relative right-shift of hemispheric asymmetry observed with age in speech in noise perception tasks in normal hearing subjects and the clinical reports of generally better audiometric speech scores obtained in RE versus LE.